Niels Otto Christensen (1917-2003) - Taagholt, J. (ARCTIC, 2004)
Niels Otto Christensen ("N.O." to his friends) passed away on 19 September 2003 in Denmark, after a very full career there and in Greenland. Following high school, N.O. commenced law studies in 1935, graduated from the University of Copenhagen in 1942, and practiced law until 1945. He then affiliated with the Greenland Office (Grønlands Styrelse) in the State Department. In 1947, he and his new bride, Birte Kold-Christensen, went to Godhavn (now Qeqertarsuaq) on Disko Island, Greenland, where N.O. served as Landsfoged (Local Governor) for North Greenland. . In 1950, the position as Landsfoged was abolished because the North and South regional councils (Landsråd) were merged into one council, situated in Godthaab (Nuuk). N.O. accordingly moved to Nuuk as Director of the Office for the Landshøvding (Governor General). In 1955 and 1956, he served as acting Landshøvding. In 1951 in Nuuk, the Christensen family met Trevor Lloyd, a professor of geography at Dartmouth College in Hanover, New Hampshire, who had served as Canadian consul in Greenland during World War II. Professor Lloyd, an advocate of increased contact between Arctic Canada and Greenland, organized an invitation for N.O. to spend half a year visiting North America. Initially he would go with Mrs. Christensen to Goose Bay (Labrador), Montreal, and Ottawa; then N.O. would separately visit Dartmouth College and spend several months visiting Inuit settlements throughout Arctic Canada. At home in Greenland in 1955, the family housed Donn Haglund, a young American geographer. Donn was writing his dissertation on the economic geography of the Nuuk District at the University of Wisconsin-Milwaukee, where he is currently professor emeritus. This stay was the beginning of a lifelong friendship between the Governor and a former Chairman of the Board of Governors at the Arctic Institute of North America. From 1957 to 1962, N.O. and Birte lived in Skodsborg, Denmark, while he served as head of office in the Ministry for Greenland. During 1958-62, he was also a ...